Development and characterization of Al2024/magnesium oxide/CNTs/hybrid composites via stir casting method - Kurt, Halil Ibrahim; Ergul, Engin; Basyigit, Aziz Baris; Oduncuoglu, Murat; Yilmaz, Necip Fazil (SAGE PUBLICATIONS LTD, 2023)
In this research, the aluminum (Al2024) matrix composites are reinforced with nano magnesium oxide (MgO) and multi-walled carbon nanotubes (MWCNTs). The aim of Al2024 alloy reinforced with MgO and MWCNTs is to reveal the effects of the reinforcement particle ratio on the microstructure and mechanical properties of the hybrid composites, to find the optimum hybrid ratio, and to form a stronger hybrid composite. The composites with the different hybrid ratios are produced via stir casting method. The theoretical and measured densities and porosity content of the composites are studied. The microstructure and fracture surface of the composites are examined by optical microscopy, scanning electron microscopy (SEM), and electron dispersive spectrum (EDS). The hardness, compression, and tensile properties of the composites are studied in this work. Results indicated that the hardness of the aluminum (Al) matrix composites (AMCs) is significantly improved after the reinforcement with MgO and carbon nanotube (CNT), and also heat treatment of T6. The stress-strain curve of the composites is tested by a material testing machine. The maximum tensile and compression strengths are obtained at Al2024-0.2 wt.% (MgO 50% + CNT 50%) the composite as 226 MPa and 684 MPa, respectively .The hardness, compression, and tensile strengths of the hybrid composites are higher than 1.51, 1.39, and 1.31 than that of the base metal. After heat treatment of T6, the maximum harness, compression, and tensile strengths are obtained by 102 HB, 730 MPa, and 277 MPa, respectively, which are 1.82, 1.49, and 1.61 times higher hardness than that that of the base Al2024 alloy. The main strengthening mechanism of nano-MgO particles and MWCNTs-reinforced Al2024/MgO/CNTs composites is observed by the precipitation strengthening mechanism.
Keywords: AMCs; MMCs; AMHCs; hybrid composites; MgO; MWCNTs; MECHANICAL-PROPERTIES; CARBON NANOTUBES; ALUMINUM; MICROSTRUCTURE; BEHAVIOR; ALLOY; FABRICATION; Engineering